The Usefulness of Selected Physical Therapy Methods in the Management of Chronic Low Back Pain: A Review of Our Experience - Taradaj, Jakub; Werszner, Anna (Physiotherapy Review, 2021)
The aim of this study was to review our recent papers on the use of selected physiotherapeutic methods in the management of chronic low back pain (LBP). Some of the procedures under discussion have a significant analgesic effect and are helpful in supporting kinesiotherapy in improving the functional state of patients with LBP. The most effective procedures for LBP include radial shock wave therapy, electrotherapy with the use of interferential currents (IFC), and the use of a high-intensity magnetic field (10 mT). To some extent, electrotherapy in the form of transcutaneous electrical nerve stimulation (TENS) and high-voltage pulsed current electrical stimulation (HVPC ES) may also be useful, although the effectiveness of these methods is significantly lower than IFC stimulation. Our research clearly shows that laser therapy, treatment using a magnetic field with lower induction (5 mT), magnetostimulation, and electrotherapy with diadynamic currents are ineffective in the management of chronic LBP.